2013
DOI: 10.1021/ja3126992
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Native State Stability in Crowded Cellular Environment Due to Protein–Protein Interactions

Abstract: The effect of cellular crowding environments on protein structure and stability is a key issue in molecular and cellular biology. The classical view of crowding emphasizes the volume exclusion effect that generally favors compact, native states. Here, results from molecular dynamics simulations and NMR experiments show that protein crowders may destabilize native states via protein-protein interactions. In the model system considered here, mixtures of villin head piece and protein G at high concentrations, vil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
201
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(223 citation statements)
references
References 41 publications
(80 reference statements)
19
201
1
Order By: Relevance
“…4 and 5). Recent advances in both the experimental (5-9, 13, 14, 16-19, 24, 26, 56, 63) and theoretical (20)(21)(22)25) aspects of macromolecular crowding allow this stabilization to be rationalized in terms of the properties of GB1 and the E. coli cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 and 5). Recent advances in both the experimental (5-9, 13, 14, 16-19, 24, 26, 56, 63) and theoretical (20)(21)(22)25) aspects of macromolecular crowding allow this stabilization to be rationalized in terms of the properties of GB1 and the E. coli cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that the effects of macromolecular crowding on globular protein stability depend on the nature of the crowder (21,25,26,70). Synthetic polymers tend to act as inert spheres and are stabilizing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] It is well established that excluded-volume interactions with crowder particles can have a significant stabilizing effect on globular proteins, as demonstrated by experiments with synthetic crowding agents such as Ficoll or dextran. 6 Today, experiments are increasingly often performed under more realistic crowding conditions, using concentrated protein solutions [7][8][9][10] or cells. 9,[11][12][13][14][15][16] In these systems, it has been shown that other interactions may dominate over the steric repulsions and lead to a net destabilization of globular proteins.…”
Section: Introductionmentioning
confidence: 99%
“…9,[11][12][13][14][15][16] In these systems, it has been shown that other interactions may dominate over the steric repulsions and lead to a net destabilization of globular proteins. [7][8][9][12][13][14]16 For a fundamental understanding of these effects, there is a need for computational approaches that permit the simulation of folding/unfolding equilibria in the presence of complex biomolecular crowding agents.…”
Section: Introductionmentioning
confidence: 99%